Polimorfisme Genetik dari Daerah 3'-Non Koding Region (3'-UTR) dari Gen HSP 70 pada Kerbau Moa (Bubalus bubalis) - Maman Rumanta; Leonard Raden Hutasoit; Rony Marsyal Kunda; Prasetyarti Utami (Jurnal Penelitian Pendidikan IPA, 2025)
The Heat Shock Protein 70 (HSP70) gene, specifically the 3-Untranslated Region (3-UTR), is critical for regulating mRNA stability and translation under heat stress. This study aimed to identify genetic polymorphisms in the 3-UTR of the HSP70 gene in Moa buffalo (Bubalus bubalis) and evaluate its potential role in heat adaptation. A total of 65 hair follicle samples (55 Moa buffalo and 10 Banten buffalo) were collected, followed by amplification by PCR and sequencing of the PCR product of the 3'-UTR regions. Alignment results from the 3'-UTR region showed the presence of 2 major polymorphic SNPs, i.e g.1904C>A, and g.1910A>G. SNP (g.1904C>A) was found to be a cytosine (C) to adenine (A) substitution mutation type, and SNP g.1910A>G an adenine (A) to guanine (G) substitution. The discovery of 2 SNPs in the 3-UTR of the HSP70 gene in Moa buffalo is very important for the development of genetic markers, helping to understand the mechanism of heat adaptation, to the conservation and improvement of livestock performance, especially Moa buffalo living in tropical environments.